SARCASM: MOCK POLITENESS IN THE BIG BANG THEORY - Nico Harared; Siti Nurani (Elite : English and Literature Journal, 2020)
Sarcasm has become an uncommon way to treat other’s faces in communication. However, the study of sarcasm has not yet been investigated thoroughly in the case of such daily illocutionary acts of the conversations. One of the sarcasm phenomena is mostly seen in the comedy situation of The Big Bang Theory. This research aims at analyzing mock politeness or sarcasm in the utterances of each character. The analysis focuses on describing the use of mock politeness in pragmatics context. The data was obtained from informal speech acts’ situations. The research carries out the descriptive qualitative method. The data was analyzed by using politeness strategy in examining the functions of mock politeness. The results show that sarcasm caused by the violation of pragmatic aspects in The Big Bang Theory releases in several types of utterances, they are: declarative, representative, and expressive. The function of sarcasm in this comedy situation mostly to create humors which are divided into several functions such as humor as a means of social critics, humor to satirize, and humor to mock.